Case report: Castleman’s disease involving the renal sinus resembling renal cell carcinoma - Zhang, Enlong; Li, Yuan; Lang, Ning (Frontiers in Surgery, 2022)
Introduction: Castleman’s disease is a rare benign lymphoproliferative disease that frequently involves mediastinal thorax and the neck lymph nodes. It very rarely affects extrathoracic presentations, with even fewer presentations in the renal sinus. Patient concerns: In this report, we present a case of a 40-year-old woman with no significant past medical history who presented Castleman’s disease arising in the renal sinus. Diagnosis and interventions: The patient visited our hospital with chief complaint of left renal sinus lesion after renal ultrasonography by regular physical examination. Subsequent abdominal computed tomography urography revealed a soft tissue mass with heterogeneous obvious enhancement in the sinus of the left kidney, which was suspected to be a renal malignant tumor. Hence, the patient underwent a left radical nephrectomy. Histological examination revealed hyperplastic lymphoid follicles in the renal sinus, and finally diagnosed as Castleman’s disease of the hyaline vascular type. Outcomes: Five days after the surgery procedure, the patient was discharged. Conclusion: Due to the low incidence of Castleman’s disease in renal sinus, there is a strong likelihood of missed diagnosis or misdiagnosis, and it is therefore important to be aware of the risk. Heightened awareness of this disease and its radiographic manifestations may prompt consideration of this diagnosis. Therefore, we explored the radiologic findings to find out some radiologic features suggesting this condition to help clinicians to schedule nephron-sparing surgery in the future.